L’art sacré entre les deux guerres : aspects de la Première Reconstruction en Picardie - Jean-Charles Cappronnier; Frédéric Fournis; Alexandra Gérard; Pascale Touzet (In Situ)
The region of Picardy in the north of France was one of the most seriously scarred by the First World War. It also witnessed a particularly interesting programme of reconstruction after the war, especially rich in the field of sacred art. This article, based on work carried out by the Historic Monuments administration and the regional Inventory service, examines four aspects of this sacred art: the modernity of the materials and techniques used; the new role of architects and church decorators; the decorations of some churches in the canton of Braine in the Aisne department; and the work of the artist Gérard Ansart.